(untitled) (Bangladesh Journal of Botany, 2021)
The chemical composition of the hydrodistilled essential oils of four Salvia spp. were analysed by GCMS. Three of them (Salvia aramiensis Rech. fil., Salvia fruticosa Mill., Salvia tomentosa Mill.) analyzed in this study grow naturally in the Hatay flora. On the other hand, S. aramiensis is an endemic plant in Hatay flora. Fourth species (Salvia officinalis L.) is not growing in the flora of Turkey, but is only cultivated. The highest essential oil content (5.31%) was found in S. aramiensis and the least 1.68% was detected in S. officinalis. Eucalyptol was the main constituent for S. aramiensis, S. fruticosa and S. tomentosa. While this component was 58.65% in S. aramiensis, it was determined as 44.70 and 34.97% in S. tomentosa and S. fruticosa, respectively. In S. officinalis, the main constituent was determined as δ-Thujone (33.83%) and camphor (21.46%). Eucalyptol has been identified as the main composition in sage species which is grown in flora. Bangladesh J. Bot. 50(4): 1173-1180, 2021 (December)